Non-invasive imaging of disrupted protein homeostasis induced by proteasome inhibitor treatment using chemical exchange saturation transfer MRI. Issue 1 (December 2018) - Zhu, Yanan; Ramasawmy, Rajiv; Johnson, Sean; Taylor, Valerie; Gibb, Alasdair; Pedley, R.; Chattopadhyay, Nibedita; Lythgoe, Mark; Golay, Xavier; Bradley, Daniel; Walker-Samuel, Simon
Abstract Proteasome inhibitors (PIs) are now standard of care for several cancers, and noninvasive biomarkers of treatment response are critically required for early patient stratification and treatment personalization. The present study evaluated whether chemical exchange (CEST) magnetic resonance imaging (MRI) can provide measurements that can be used as the noninvasive biomarkers of proteasome inhibition, alongside diffusion MRI and relaxometry. The sensitivity of human colorectal carcinoma cells to the PI Ixazomib was assessed viain vitro andin vivo dose-response experiments. Acutein vivo response to Ixazomib was assessed at three dosing concentrations, using CEST MRI (amide, amine, hydroxyl signals), diffusion MRI (ADC) and relaxometry (T1, T2 ). These responses were further evaluated with the known histological markers for Ixazomib and Bradford assayex vivo . The CEST signal from amides and amines increased in proportion to Ixazomib dose in colorectal cancer xenografts. The cell lines differed in their sensitivity to Ixazomib, which was reflected in the MRI measurements. A mild stimulation in tumor growth was observed at low Ixazomib doses. Our results identify CEST MRI as a promising method for safely and noninvasively monitoring disrupted tumor protein homeostasis induced by proteasome inhibitor treatment, and for stratifying sensitivity between tumor types.